Having Used Self-Control Increases Criminality - Gailliot, Matt (Advances in Social Sciences Research Journal, 2014)
Ample work demonstrates that poor self-control is a major contributor to criminality. Other work indicates that self-control is impaired or fatigued following use. Self-control fatigue therefore might increase criminal tendencies. Participants either did or did not use self-control by controlling their attention. They later indicated perceptions of their likelihood to engage in criminal acts (e.g., stealing, buying illegal drugs). Participants who had used (v did not use) self-control indicated a greater perceived likelihood of committing crimes. This effect did not appear attributable to general risk taking, mood or arousal, or socially desirable responding.